1996
DOI: 10.1007/s004360050133
|View full text |Cite
|
Sign up to set email alerts
|

Production of interleukin 10 during malaria caused by lethal and nonlethal variants of Plasmodium yoelii yoelii

Abstract: We investigated the induction of T-helper cell subsets during the course of lethal or nonlethal bloodstage Plasmodium yoelii 17X infection in C57BL/6 mice, which are relatively susceptible to these intraerythrocytic parasites. C57BL/6 mice infected with the nonlethal variant (PyNL) showed a moderate level of parasitemia and resolution of primary acute infection by week 4. Mice infected with the lethal variant (PyL) developed fulminating parasitemia and ultimately died. T-helper subset function was assessed dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 39 publications
5
33
1
Order By: Relevance
“…Despite clear evidence that anti-inflammatory cytokines and/or regulatory T cells inhibit the clearance of PyL pRBC (15,16,21,22,35,36), this study has not shown any role for T cells, NK cells, or IFN-␥ in the control of acute P. yoelii infection. However, given the absence of MHC expression on the majority of red blood cells (19), it is probable that neither T cells nor NK cells play the terminal effector role in parasite killing.…”
Section: Vol 75 2007 Control Of Lethal and Nonlethal P Yoelii Infecontrasting
confidence: 81%
See 2 more Smart Citations
“…Despite clear evidence that anti-inflammatory cytokines and/or regulatory T cells inhibit the clearance of PyL pRBC (15,16,21,22,35,36), this study has not shown any role for T cells, NK cells, or IFN-␥ in the control of acute P. yoelii infection. However, given the absence of MHC expression on the majority of red blood cells (19), it is probable that neither T cells nor NK cells play the terminal effector role in parasite killing.…”
Section: Vol 75 2007 Control Of Lethal and Nonlethal P Yoelii Infecontrasting
confidence: 81%
“…In contrast, depletion of macrophages with clodronate liposomes markedly reduced the ability of the mice to control acute PyL or PyNL infection. Taking these data together with previously published studies in which rapid induction of IL-10 or TGF-␤ and/or early activation of regulatory T cells were found to prevent control of PyL infections (15,16,22,35,36) suggests that these immunoregulatory pathways may act directly to suppress the effector functions of innately activated macrophages. Somewhat surprisingly, effector T-cell activation, expansion, and function were very similar during lethal and nonlethal P. yoelii infections.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…It has been shown that mice infected with Pb NK65 develop severe parasitemia and die within 2 wk, although mice infected with Pb XAT or Py 17X cure spontaneously around 3 wk of infection (15,17). To examine whether primary infection with each of the two nonlethal parasites can induce protective immunity against Pb NK65 lethal infection, groups of C57BL/6 (B6) mice were infected with Pb XAT or Py 17X then challenged with Pb NK65 on day 30 after primary infection.…”
Section: Infection With Pb Xat But Not Pb 17x Induces Protective Immumentioning
confidence: 99%
“…IFN-␥ and IL-10 have been shown to be associated with protection and exacerbation during P. berghei and P. yoelii malaria (17,18).…”
Section: Enhanced Levels Of Il-10 Mrna During Coinfection and Nonlethmentioning
confidence: 99%